Digitalisasi Pengelolaan Homestay Melalui Pelatihan Aplikasi Akuntansi Berbasis Android Pada Masyarakat Di Desa Wisata Pelaga - I Gede Dirga Surya Arya Widhyadanta; Ni Luh Gde Sari Dewi Astuti (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Accounting information provides a reliable basis for making financial decisions related to small business operations, such as market trends, pricing and other decisions. Due to the homestay owner's lack of understanding of the business process in preparing the business financial report, the company's operating funds and personal funds are still separated as one entity, and performance is not properly communicated. The purpose of this training activity is to assist homestay owners in the preparation and preparation of financial reports through training using smartphone enabled applications and to facilitate homestay owners to learn and use financial reporting applications. Training activities for homestay owners of Pelaga Tourist Village will be conducted using methods of lectures, tutorials, discussions and simulations. The training be conducted online using Zoom meetings. 17 homestay owners participated in the training. Survey results showed that 88% of participants were willing to use a digital financial reporting application (in this case his UKM application) to obtain transactions and financial reports for each host family . Only 16% of participants had knowledge of 'UKM' prior to the training. Additionally, activity participants were also able to use her UKM application to prepare financial reports, as all participants attempted to make and enter financial transactions on her “UKM” application.